Preface - Almeida, João P. (2019)
In 2019, APDIO has organized the twentieth Portuguese national conference of Operational Research (OR)—the IO series. With this long-lasting list of events, success has been the main takeaway from each unique occurrence. With a growing number of members, also with growing enthusiasm, the conference series has reached most regions in themainland country.Recently, the frequency of the conference was increased, while maintaining the same attendance and quality of work. Outreach of the conference to OR researchers from different nationalities is also increasing and bringing an international feel to the events. Year after year, keynote speakers from industry and from other European societies have joined us to share knowledge and current research and practice of OR. Our national OR discussion forum has influenced, as well, a growing number of national members attending and presenting in international OR conferences and participating actively in EURO Working Groups. However, besides validating our OR research, our national conferences always promote a very strong, very Portuguese social occasion. A true networking event is where work and social well-being are sustained—and looked forward—event after event. With this book as the last physical milestone of IO2019, we perpetuate the results from this event and invite all our members,